THE RELATIONSHIP BETWEEN NURSES' RESPONSE TIME AND PATIENTCARE QUALITY IN THE EMERGENCY DEPARTMENT OF PROF. DR.SOEKANDAR REGIONAL HOSPITAL, MOJOKERTO REGENCY - Heti Aprilin; Edy Siswantoro; Nuris Kushayati; Fitria Windy Lestari (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Background: While rapid nurse response time is a critical performance indicator inEmergency Departments (ED) to ensure patient safety, perceived service quality isincreasingly recognized as a multifactorial construct. Technical efficiency alone maynot fully align with the qualitative expectations of patients. Objective: This study aimsto analyze the relationship between nurses' response time and patient care quality inthe ED of Prof. Dr. Soekandar Regional General Hospital, Mojokerto Regency.Methods: An analytic observational study with a cross-sectional design wasconducted. A sample of 144 respondents was selected via simple random sampling.Data were collected using observation sheets and a validated multidimensional servicequality questionnaire (Cronbach’s alpha = 0.84), then analyzed using the SpearmanRank correlation test. Results: The majority of respondents (95.8%) experienced afast response time (≤5 minutes), yet 61.1% perceived the service quality as only